The ARTificial revolution. Introducing generative artificial intelligence tools into artistic education - Andrés Torres-Carceller (Revista Catalana de Pedagogia)
This article presents an experience of integrating generative artificial intelligence (AI) technologies in artistic education in the Primary School Teaching degree course. The aim of combining AI algorithms with traditional image editing techniques is not only to teach instrumental skills but also to foster a critical understanding of the limitations and risks associated with these technologies, promoting responsible and ethical use. The ability of AI to rapidly generate original content from text, images, video, and code, presents a complex landscape of opportunities and challenges. AI is redefining human cognitive processes and creativity, making it crucial to emphasise the importance of maintaining human intelligence as an irreplaceable complement to technology. The implementation of generative AI in art education not only enriches visual and aesthetic learning but also prepares students to contribute critically and creatively to the intersection of art and technology, equipping them with essential skills for innovation in their artistic practices.